Constructive Alignment in Higher Education: Curriculum Design, Assessment and Inclusive Practices in Nepal - Chaudhary, Anju Kumari (Chhahari छहारी, 2026)
Constructive alignment, a pedagogical concept proposed by John Biggs, has emerged as a foundational framework for improving teaching, learning, and assessment in higher education. Rooted in constructivist learning theory, it emphasizes the alignment of learning outcomes, instructional strategies, and assessment tasks to promote deep learning. This article examines the relevance and application of constructive alignment within the context of Nepalese higher education, with special reference to Tribhuvan University (TU). It highlights how curriculum design, formative and summative assessment, and inclusive practices can be restructured to foster learner-centered education, enhance employability, and ensure equity. Using a qualitative review of literature, educational policies, and institutional practices, the paper identifies gaps between theoretical principles and actual implementation in Nepal. It argues that integrating constructive alignment into TU’s curriculum and assessment systems can help overcome traditional rote learning tendencies, improve feedback culture, and advance the goals of inclusive, outcome-oriented higher education in Nepal.